Benin : Staff Report for the Second Review and the Second-Year Program Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2001)
Benin's economic and financial performance under the first-year program supported by the poverty reduction and growth facility was satisfactory. The resumption of structural reform implementation is essential for the authorities to improve resource allocation and meet their objective of accelerating growth to 7 percent over the medium term. To accelerate economic growth and improve service delivery, a broad consensus is emerging on the need to draw private expertise and capital into key public enterprises, either through privatization or different forms of public-private partnerships.